An annual survey of work- induced accidents in injured farmers referring to health centers in Bam - A Esmaeili; R Vazirinejad; F Shahrokhi (طب کار)
Abstract Background: Accidents are one of the most important health problems worldwide. According to world health organization (WHO), 3.5 million people die from unintentional injuries each year. Occupational injuries are the subject for the new challenges in the world. Economic burdens of occupational diseases and injuries compared to other diseases such as cancer, cardiovascular diseases, Alzheimer disease and AIDS are very high. Materials and Methods: This is a one-year prospective survey of accidents among injured Bam farmers referring to health center (2005-2006). Data concerning demographic variables, accident conditions, and injury characteristics were collected using a questionnaire. The data were analyzed using SPSS and Excel. Parametric and non-parametric tests were used to compare groups. Results: A total of 70 injuries reported. Mean age was 37.2 years. The results showed that fall from palm trees was the most common mechanism of injury (41.4%). Legs and hands were the main injured area (61.4%). Most of the injuries occurred in the September and March (25.7% and 14.3%), respectively. Conclusion: Training, use and access to personal protective equipment especially safety belt, are important in prevention of accidents among Bam farmers to help with reducing of accidents and resulting injuries.